Lupus Podocytopathy in an Adolescent Nigerian Girl: A RareRenal Manifestation of SLE (Western Journal of Medical and Biomedical Sciences, 2025)
Lupus podocytopathy (LP) is a rare renal manifestation of systemic lupus erythematosus (SLE), characterized by nephrotic syndrome and minimal change disease or focal segmental glomerulosclerosis in the absence of immune complex deposition. It is often underrecognized, especially in low-resource settings due to limited access to advanced diagnostic tools. We report the case of a 15-year-old Nigerian female who presented with a 10-month history of recurrent body swelling without other systemic features of SLE. Initial evaluation revealed nephrotic-range proteinuria (6.94 g/24h), hypoalbuminemia (13.1 g/L), positive ANA (1:160), and anti-dsDNA (1:172), with normal renal function. Renal biopsy showed features consistent with minimal change disease and no immune deposits on immunohistochemistry. A diagnosis of lupus podocytopathy was made. She was treated with high dose prednisolone and mycophenolate mofetil (MMF), achieving partial remission by 6 months and complete remission by 12 months. Maintenance therapy with azathioprine was commenced thereafter, with sustained remission. In Conclusion, Lupus podocytopathy should be considered in young patients presenting with nephrotic syndrome and positive lupus serologies even in the absence of other systemic manifestations. Early diagnosis and prompt immunosuppressive therapy can result in favourable outcomes. This case underscores the importance of renal biopsy and serologic testing in evaluating atypical lupus presentations inAfrican clinical settings.
Keywords: Adolescent; Immunosuppression Lupus podocytopathy; Minimal Change Disease; Nephrotic Syndrome; Nigeria; Systemic Lupus Erythematosus